2019
DOI: 10.1007/jhep10(2019)267
|View full text |Cite|
|
Sign up to set email alerts
|

Constraints on the quartic Higgs self-coupling from double-Higgs production at future hadron colliders

Abstract: We study the indirect constraints on the quartic Higgs self-coupling that arise from double-Higgs production at future hadron colliders. To this purpose, we calculate the two-loop contributions to the gg → hh amplitudes that involve a modified h 4 vertex. Based on our results, we estimate the reach of a pp collider operating at 27 TeV and 100 TeV centre-of-mass energy in constraining the cubic and quartic Higgs self-couplings by measurements of double-Higgs and triple-Higgs production in gluon-fusion.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
52
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(53 citation statements)
references
References 63 publications
0
52
1
Order By: Relevance
“…Indirect constraints on the Higgs self interactions have also been studied for precision electroweak observables and loop level corrections to Higgs cross sections (e.g. [19][20][21][22][23][24][25][26]), which also have sensitivity but are more model dependent.…”
Section: Introductionmentioning
confidence: 99%
“…Indirect constraints on the Higgs self interactions have also been studied for precision electroweak observables and loop level corrections to Higgs cross sections (e.g. [19][20][21][22][23][24][25][26]), which also have sensitivity but are more model dependent.…”
Section: Introductionmentioning
confidence: 99%
“…(2.1). Of course this pattern changes once electroweak corrections, part of which have been calculated recently [29,67], are included. In order to allow for comparisons and cross checks, we implemented both the m t → ∞ limit as well as the amplitudes with full m t -dependence at NLO.…”
Section: Overview Of the Calculationmentioning
confidence: 99%
“…Recent phenomenological studies about the precision that could be reached for the trilinear coupling at the (HL-)LHC and future hadron colliders can be found for example in Refs. [26][27][28][29][30][31][32][33][34][35][36].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Much remains to be understood about the Higgs sector. On the collider side, measuring the Higgs cubic and quartic couplings through double or triple Higgs production, both non-resonant as well as resonant, is an extremely difficult but central goal of future experiments (see e.g., [73][74][75][76][77][78][79]). While any deviation of the shape of the Higgs potential from what is expected within the Standard Model (SM) would hint to new physics, the sensitivities of such collider studies are found to be rather low.…”
Section: Introductionmentioning
confidence: 99%